Pengalaman Tim Multidisiplin Melayani Lansia di Panti: Studi Deskriptif Fenomenologis - Royani Royani; Achir Yani Syuhaimie Hamid; Etty Rekawati; Ede Surya Darmawan (Faletehan Health Journal, 2025)
Elders need friendly, competent, and responsive staff and an organized, clean and welcoming environment. However, preliminary interviews with multidisciplinary teams in nursing homes showed they sometimes felt bored. This study aimed to understand the multidisciplinary teams’ experiences of caring for elders in nursing homes. This is descriptive qualitative research used semi-structured interviews, forum group discussions (FGDs) with 64 participants in Jakarta provincial government-owned nursing homes, document analysis, and observations. The data were collected from September 2022 to July 2023 and analyzed using Colaizzi's measures. The results showed the elders at the nursing homes experienced physical, psychological, behavioral and social changes, where some of them came from poverty or neglect background. Their needs included biological, psychological, social, and spiritual aspects. The multidisciplinary teams felt a variety of emotions when serving the elders, such as happiness, sadness, and sometimes annoyance. Some also felt “reframing,” a feeling of being forced due to no other choice. Therefore, cultivating characters such as empathy, compassion, patience, and sincerity in providing the care is important. Changes in elders with different backgrounds require integrated support. Nursing home management should provide periodic training to the multidisciplinary teams; thus, the service quality can be improved.